A portable reflected-sunlight spectrometer for CO2 and CH4 - Löw, Benedikt; Kleinschek, Ralph; Enders, Vincent; Sander, Stanley P.; Pongetti, Thomas J.; Schmitt, Tobias; Hase, Frank; Kostinek, Julian; Butz, André (Atmospheric measurement techniques, 2023)
Mapping the greenhouse gases (GHGs) carbon dioxide (CO2) and methane (CH4) above source regions such as urban areas can deliver insights into the distribution and dynamics of local emission patterns. Here, we present the prototype development and an initial performance evaluation of a portable spectrometer that allows for measuring CO2 and CH4 concentrations integrated along a long (> 10 km) horizontal path component through the atmospheric boundary layer above a target region. To this end, the spectrometer is positioned at an elevated site from which it points downward at reﬂection targets in the region, collecting the reﬂected sunlight at shallow viewing angles. The path-integrated CO2 and CH4 concentrations are inferred from the absorption ﬁngerprint in the shortwave-infrared (SWIR) spectral range. While mimicking the concept of the stationary California Laboratory for Atmospheric Remote Sensing - Fourier Transform Spectrometer (CLARS-FTS) in Los Angeles, our portable setup requires minimal infrastructure and is straightforward to duplicate and to operate in various locations.
Gesehen am 02.08.2024
Im Titel ist "2" und "4" tiefgestellt